Perpetrator Pathology and the Entitlement Cascade - Nsiangani, Kibavuidi (CEMA -USK, 2020)
Abstract This article develops a decolonial psychological model of the entitlement cascade: the process by which repeated domination is reframed as a right, explaining the persistence of the trans-Atlantic deportation system and genocidal regimes. The research question is what psychological and cultural machinery normalizes this violence and the undercounting of victims. Building on prior work on the Dark Tetrad (narcissism, Machiavellianism, psychopathy, sadism) in imperial institutions, our contribution is the formalization of the cascade in a four-stage process and the mapping of a three-tier collaborator spectrum (coerced, ambivalent, converted) linked to Puppet Syndrome. The methodology is a comparative reading of cases (Kongo, Congo Free State, postcolonial regimes) integrating demographic constraints. Findings reveal the cascade stages (exceptionalisation, normalisation, moralisation, epistemic locking) and cross-period continuities. The conclusion is that the stubborn insistence on the documented 1.8 million captives (a floor, with plausible totals of 8–12 million) is a key symptom of perpetrator psychology—an institutional lowballing that makes continuous killing manageable. The study outlines clinical and pedagogical applications for reparative justice.-----Keywords: Entitlement Cascade, Decolonial Psychology, Dark Tetrad, Puppet Syndrome, Trans-Atlantic Deportation, Epistemic Locking. Keywords: Entitlement Cascade, Decolonial Psychology, Dark Tetrad, Puppet Syndrome, Trans-Atlantic Deportation, Epistemic Locking. Résumé (FR) Cette recherche développe la psychologie décoloniale de la cascade de l’entitlement (droit perçu à dominer) pour expliquer la pérennité du système de déportation transatlantique et des régimes génocidaires. Le contexte est la persistance de la violence institutionnelle au-delà des facteurs économiques. La question de recherche est de comprendre le mécanisme psychologique qui normalise la violence de masse et le sous-dénombrement des victimes. Notre contribution est la formalisation de cette cascade en un processus en quatre étapes, lié à la Tétrade Sombre (narcissisme, machiavélisme, psychopathie, sadisme) dans les structures étatiques, et l'établissement d'un spectre de collaborateurs (du contraint au converti). La méthodologie repose sur une lecture comparative de cas historiques (Kongo, Congo Free State) et l'intégration des reconstructions démographiques. Les résultats décrivent un processus en quatre phases (exceptionnalisation, normalisation, moralisation, verrouillage épistémique). La conclusion est que l'insistance sur le chiffre de 1,8 million de captifs (au lieu d'une fourchette plausible de 8 à 12 millions) est un symptôme de cette psychologie de l'agresseur, appelant à des outils cliniques et politiques pour désarmer ces mécanismes de défense. Mots-clés : Cascade de l'Entitlement, Psychologie Décoloniale, Tétrade Sombre, Syndrome du Marionnette, Déportation Transatlantique, Verrouillage Épistémique